Endoscopic management of intravesical foreign body: A challenging condition. - Muhammad Farhan; Aftab, Malik; Sharif, Khurram; Muhammad Saad; Ahmed, Faraz; Muhammad Jamal (International Journal of Endorsing Health Science Research, 2022)
Background: Unusual genitourinary activity is categorized by the genital deposit of foreign objects. It has been known for centuries and common etiological factors include sexual stimulation. Psychiatric disorders and intoxication may also be associated. Foreign body retrieval and the evaluation of psychosocial factors are involved in management. This study intends to present a 'hair pin' case as a foreign body in the bladder. Methodology: A 25-year-old female presented to the urology outpatient clinic in early pregnancy with a history of manually inserting hairpin into the urinary bladder through her urethra four years back. She lost to follow up during pregnancy and then presented again after C-section. A plain abdominal film of the kidneys, ureters, and bladder (KUB) confirmed the location of the hairpin and large stone around it in the urinary bladder. Results: The patient underwent endoscopic removal of foreign body and stone. At cystoscopy urethra was normal, but in the urinary bladder, there was a hairpin with stone formation at its proximal end, and distal portion of the hairpin was embedded in the bladder neck. The hairpin was pushed back in the bladder to separate from the bladder neck, followed by stone fragmentation using a stone punch. After complete removal of stones, the hairpin was aligned in the line of the urethra and removed with the help of forceps. Conclusion: Depending on the nature of the foreign body and available expertise, methods for removing intravesical foreign bodies are opted. Mostly endoscopic techniques are used for retrieval of intravesical foreign bodies without resorting to open surgery.